Electromagnetic compatibility of semiconductor structures with a two-dimensional electron layer - Kravchenko, Volodymyr; Knyazev, Volodymyr; Serkov, Aleksandr; Breslavets, Vitaliy; Yakovenko, Igor (Національний технічний університет "Харківський політехнічний інститут", 2019)
The subject matter is the mechanisms of interaction of the flow of charged particles with the surface plasmons of a two-dimensional electron layer (2D) due to the action of external pulsed electromagnetic radiation (EMP).The aim is obtaining design relations that determine to what degree the instabilities of natural vibrationsof a two-dimensional electronic layer of a semiconductor structure may influence the performance of semiconductor devices. The objectives area model of occurrence of reversible failures of radio products arising from the transformation of energy of currents induced by external pulsed radiation to excite electrostatic oscillations of a two-dimensional electronic layer of semiconductor structures. The methodsused areanalytical methods for solving electrodynamics (Maxwell) equations and material equations in the framework of kinetic approach. The following resultshave been obtained: The mechanisms of interaction of the flow of charged particles with the natural electromagnetic vibrations of a two-dimensional electron gas occurring due to the presence of a potential barrier at the interface have been studied. Investigations of functioning of semiconductor components of radio products (structures with two-dimensional electron gas) under the influence of strong pulsed electromagnetic fields have been carried out. A kinetic equation describing the change in thenumber of electromagnetic oscillations of such a system has been obtained. The solution of the equation has been found, which allows determining the influence of the barrier on the instability increment of surface vibrations as well as the contributions of the transmitted and reflected components of the particle flux to the increment. Equations for the increment of instabilitie sallow us to determine the energy loss of the induced currents on the excitation of natural oscillations i.e. the emergence of a mode of oscillation generation, which is characterized by a change in the volt-ampere characteristics of radio devices. Conclusion. A comparative analysis of the instabilities of vibrations of structures with a two-dimensional electron gas has been carried out under conditions when the interaction of waves and particles is randomand deterministic. It is shown that the differences in the expressions for increments are associated with a change in the size of the region of interaction of waves and particles. Differences in the influence of the potential barrier on the increment are established in cases where the interaction of surface plasmons and charged particles is determined or has the character of random collisions. The mechanisms of the influence of the boundary on the interaction of surface electromagnetic waves and electrons in the presence of a potential barrier are determined. I ntrinsic electromagnetic oscillations of a two-dimensional electron layer are taken as research objects. The results obtained in the work can be used to assess the operability of electronic equipment in millimeter and submillimeter ranges under the influence of pulsed electromagnetic fields.

Предметом вивчення є процес аналізу механізмів взаємодії потоку заряджених частинок з поверхневими плазмонами двовимірного електронного шару (2D), зумовлені впливом зовнішнього імпульсного електромагнітного випромінювання (ЕМВ). Метою є отримання розрахункових співвідношень, що визначають ступінь впливу нестійкостей власних коливань двовимірного електронного шару напівпровідникових структур на працездатність напівпровідникових приладів. Об'єктом дослідження є: модель виникнення оборотних відмов електрорадіовиробів, що виникають внаслідок трансформації енергії наведених зовнішнім імпульсним випромінюванням струмів на збудження електростатичних коливань двовимірного електронного шару напівпровідникових структур. Використовувані методи: аналітичні методи рішення рівнянь електродинаміки (Максвелла) і матеріальних рівнянь в рамках кінетичногопідходу. Отримані наступні результати: Досліджено механізми взаємодії потоку заряджених частинок з власними електромагнітними коливаннями двовимірного електронного газу, виникнення якого обумовлено наявністю потенційного бар'єру на межі поділу середовищ. Проведено дослідження функціонування напівпровідникових комплектуючих електрорадіовиробів (структур з двовимірним електронним газом) в умовах впливу сильних імпульсних електромагнітних полів. Отримано кінетичне рівняння, що описує зміну числа електромагнітних коливаньтакої системи. Наведено його рішення, що дозволяє визначати вплив величини бар'єру на інкремент нестійкості поверхневих коливань; внесок в величину інкременту пройшла і відбитої компонент потоку частинок. Вирази для інкременту нестікостей дозволяють визначати енергетичні втрати наведених струмів на збудження власних коливань, тобто появі режиму генерації коливань, який характеризується зміною вольт - амперних характеристик радіовиробів. Висновки. Проведено порівняльний аналіз нестійкостейколивань структур з двовимірним електронним газом в умовах, коли взаємодія хвиль і частинок носить випадковий і детермінований характер. Показано, що відмінності в виразах для інкрементів пов'язані зі зміною розмірів області взаємодії хвиль і частинок. Встановлено відмінності впливу потенційного бар'єру на величину інкрементув випадках, коли процес взаємодія поверхневих плазмонів і заряджених частинок детермінований або носить характер випадкових зіткнень. Визначено механізми впливу кордону на взаємодію поверхневих електромагнітних коливань і електронів при наявності потенційного бар'єру. Як об'єкти досліджень розглянуті власні електромагнітні коливання двовимірного електронного шару. Результати, отримані в роботі, можуть бути використані при оцінці працездатності радіоелектронноїапаратури міліметрового і субміліметрового діапазонів в умовах впливу імпульсних електромагнітних полів.
Електромагнітна сумісність напівпровідникових структур з двовимірним електронним шаром
Keywords: electromagnetic fields; vibrations; semiconductor; kinetic instabilities; електромагнітні поля; коливання; напівпровідник; кінетичні нестійкості